How Can Cognitive Reserve Promote Cognitive and Neurobehavioral Health?. (14th October 2021) - Stern, Yaakov
Abstract: Objective: This review is aimed at understanding how cognitive reserve and related concepts contribute to promoting neurobehavioral and cognitive health, consistent with goal of the 2020 national academy of neuropsychology (NAN) Annual Meeting. Research indicates that lifestyle factors such as achieving educational and work milestones, participating in leisure and social activities and IQ are all associated with reduced risk of cognitive decline in normal aging and of developing dementia. Many of these lifestyle factors have also been associated with better cognition in other psychiatric and neurological conditions. The cognitive reserve hypothesis posits that these lifestyle factors result in individual differences in the flexibility and adaptability of brain networks that may allow some people to cope better than others with age- or dementia-related brain changes. Recent evidence also supports the idea that specific genetic and lifestyle factors may help preserve a healthy brain or enhance brain reserve, a process that has been called brain maintenance. The complementary concept of brain reserve posits that structural brain features can guard against dementia and related conditions. This review defines these theoretical concepts, their research basis, how they are studied and their clinical applications. Conclusion: Evidence supports the concept of reserve, which can be influenced by experiences in every stage of life. Focused research in this area can maximize the chance for successful intervention.